The effects of microbiota abundance on symptom severity in Parkinson’s disease: A systematic review - Papić, Eliša; Rački, Valentino; Hero, Mario; Tomić, Zoran; Starčević-Čižmarević, Nada; Kovanda, Anja; Kapović, Miljenko; Hauser, Goran; Peterlin, Borut; Vuletić, Vladimira (Frontiers in Aging Neuroscience, 2022)
Introduction: Parkinson’s disease (PD) is neurodegenerative disease with a multifactorial etiopathogenesis with accumulating evidence identifying microbiota as a potential factor in the earliest, prodromal phases of the disease. Previous research has already shown a significant difference between gut microbiota composition in PD patients as opposed to healthy controls, with a growing number of studies correlating gut microbiota changes with the clinical presentation of the disease in later stages, through various motor and non-motor symptoms. Our aim in this systematic review is to compose and assess current knowledge in the field and determine if the findings could influence future clinical practice as well as therapy in Parkinson’s disease. Methods: We have conducted a systematic review according to PRISMA guidelines through MEDLINE and Embase databases, with studies being selected for inclusion via a set inclusion and exclusion criteria. Results: 20 studies were included in this systematic review according to the selected inclusion and exclusion criteria. The search yielded 18 case control studies, 1 case study and 1 prospective case study with no controls. The total number of PD patients encompassed in the studies cited in this review is 1511. Conclusion: The link between gut microbiota and neurodegeneration is a complex one and it depends on various factors. The relative abundance of various microbiota taxa in the gut has been consistently shown to have a correlation with motor and non-motor symptom severity. The answer could lie in the products of gut microbiota metabolism which have also been linked to PD. Further research is thus warranted in the field, with a focus on the metabolic function of gut microbiota in relation to motor and non – motor symptoms.